The Influence of Love of Money, Idealism, Religiosity and Gender on the Ethical Perception of Tax Evasion with Machiavellian as Moderation - Whittleliang Hakki, Tandry; Friska, Friska; Fanesyah, Fanesyah (DINASTI RESEARCH, 2025)
This study aims to examine the influence of Love of Money, Idealism, Religiosity, and Gender on the ethical perception of tax evasion, and to test whether Machievalian can strengthen the influence of Love of Money, Idealism, Religiosity, and Gender on the ethical perception of tax evasion. The type of data used in this study is primary data in the form of company financial statements that are used as samples. The research method used in this study is the quantitative research method. Samples were selected using the purposive sampling method. For hypothesis testing, this study uses multiple linear regression analysis. Based on the results of the research expected in this study are: Love of money is associated with the ethical perception of tax evasion, Idealism is associated with the perception of the ethics of tax evasion, Religiosity is associated with the perception of the ethics of tax evasion, Gender is associated with the perception of the ethics of tax evasion, Marchiavellian strengthens the influence of love of money on the perception of the ethics of tax evasion, Marchiavellian strengthens the influence of Idealism on the perception of ethics tax evasion, Marchiavellian strengthens the influence of Religiosity on the ethical perception of tax evasion, Marchiavellian strengthens the influence of Gender on the perception of tax evasion ethics.